Birthweight and Preterm Birth in Relation to Indicators of Childhood Asthma - Kitaw Demissie; Pierre Ernst; Lawrence Joseph; Margaret R Becklake (Canadian Respiratory Journal)
BACKGROUND: Early life events may have long term consequences on respiratory health including the risk of developing asthma.